TrypInDB: A searchable online resource of small molecule inhibitors against Trypanosoma sp. (October 2020) - Vijayakumar, Saravanan; Ranjan, Ravi; Kumar, Rishikesh; Das, Pradeep
Abstract: African Trypanosomiasis and American Trypanosomiasis are the diseases affecting more than thousands of people yearly and more than twenty-five million people risk acquiring the disease. The treatment for the disease is generally expensive, and most of the available drugs are of high-toxicity and cause fatal side-effects. Hence, there is a constant need for finding new treatment strategies for Trypanosomiasis. Combination therapy and repurposing or redesigning of existing inhibitors for new drugs are of high importance to address these hurdles, particularly the drug resistance. Hence, here we report TrypInDB, a searchable online resource of small molecule inhibitors having a varying degree of activity towards Trypanosoma sp. Information of about >14, 000 small molecules from >700 published research articles was collected and made as an easy-to-search database. Four major sets of information were made available for each collected inhibitors viz., General information (activity values; source of the inhibitors; enzyme targets; etc., ), Structural information, Toxicity information, and Literature information. More than 25 different information about each inhibitor were collected or predicted and made accessible for searching. The database is designed to be queried easily with multiple-field filters with the provisions to perform sub-structure search and similar FDA approved drug searches. The database supports the easy export of queried records and structure in multiple formats. In addition, the TrypInDB is actively integrated into LeishInDB. We believe that the scope of TrypInDB permits the research community to exploit the available data for repurposing the inhibitors as well as for the investigation of new therapeutics. Database URL: http://trypindb.biomedinformri.com/ Graphical abstract: Unlabelled Image Highlights: Information of >14, 000 small-molecules having varying degree of activity against Trypanosoma sp Manually collected from 775 published articles Easy-to-use interface with dynamic multi-field search options Includes chemical sub-structure search and data export options in multiple formats